Editorial: Contract cheating in Canada - Usick, Brandy; Stoesz, Brenda M (Canadian Perspectives on Academic Integrity, 2021)
We present the second issue of the fourth volume of the Canadian Perspectives on Academic Integrity (CPAI). This issue consists of an invited historical article about contract cheating and the proceedings from the second Canadian Symposium on Academic Integrity (CSAI) 2021 hosted virtually by Thompson Rivers University, Kamloops, British Columbia, Canada.